2-D RESISTIVITY IMAGING AND HYDROGEOCHEMICAL ANALYSIS FOR LEACHATE MIGRATION AT DUMPSITES IN SOUTH-SOUTH NIGERIA - Irunkwor, C; Abanjo, N (International Journal of Environmental Sciences, 2022)
Vertical electrical sounding, 2-D tomography and hydrogeochemical analysis was applied to investigate dumpsite leachate plume generation, migration and its impact on the surrounding soil and groundwater aquifer at a municipality in the Western Niger Delta. Twelve vertical electrical sounding (VES) was investigated using the Mini-Res Resistivity Meter with the Schlumberger array. The VES survey result was interpreted with Winglink software. Five hand-dug well water and 5 tap/borehole water samples was collected for hydrogeochemical analysis using the sterile plain bottles and 1-litre plastic bottles. Resistivity results delineated 5 layers of lateritic topsoil, sandy clay, fine coarse-sand, medium coarse-sand and coarse sand. The VES and 2-D tomography mapped and identified 2 distinct zones viz:zone of low resistivity of 91Ωm and 394Ωm at depth of 5m to >28m indicating area of leachate contaminant plume and zone of high resistivity value of 422Ωm and 5102Ωm suspected to be dumpsite gases such as NH3, CH4, SO2 and CO2. The 2-D resistivity imaging also revealed that the generated dumpsite leachate contaminant plume was migrating from the Northern part of the burrow-pit dumpsite towards its Eastern part and to the Northern part of the dumpsite at Scot road/Sakponba road. Hydrogeochemical parameter results showed that colour, pH, iron, Lead and coliform bacteria exceeded permissible standard indicating that the leachate plume has migrated to the groundwater aquifer. Closed municipal landfill whose base is made of concrete and paved surfaces should be adopted in the area to prevent leaching of poisonous substances into groundwater aquifer.